2012
DOI: 10.1016/j.ijrobp.2012.02.041
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive/Nonadaptive Proton Radiation Planning and Outcomes in a Phase II Trial for Locally Advanced Non-small Cell Lung Cancer

Abstract: Purpose To analyze dosimetric variables and outcomes after adaptive replanning of radiotherapy during concurrent high-dose protons and chemotherapy for locally advanced non-small cell lung cancer (NSCLC). Methods and Materials Nine of 44 patients with stage III NSCLC in a prospective phase II trial of concurrent paclitaxel/carboplatin with proton radiation [74 Gy(RBE) in 37 fractions] had modifications to their original treatment plans after re-evaluation revealed changes that would compromise coverage of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(67 citation statements)
references
References 16 publications
(31 reference statements)
3
63
0
Order By: Relevance
“…10 Although APT is not yet widespread due to the limited deployment of volumetric imaging systems at proton centers, dose adaptation of proton treatments promises improved target coverage and normal tissue sparing. 11 Daily volumetric imaging with CBCT is a good candidate for APT as well as for image-guided proton therapy. However, there have been few studies on CBCT imaging for APT.…”
Section: Introductionmentioning
confidence: 99%
“…10 Although APT is not yet widespread due to the limited deployment of volumetric imaging systems at proton centers, dose adaptation of proton treatments promises improved target coverage and normal tissue sparing. 11 Daily volumetric imaging with CBCT is a good candidate for APT as well as for image-guided proton therapy. However, there have been few studies on CBCT imaging for APT.…”
Section: Introductionmentioning
confidence: 99%
“…Proton therapy for lung cancer may be better able to spare critical structures than intensity modulated photon radiation therapy (IMRT) (1)(2)(3)(4)(5)(6). Passive scattering proton therapy (PSPT), however, relies on 3-dimensional treatment planning (with its inherent limitations) and requires typically 0.5 to 1 cm smearing plus other uncertainty margins (7).…”
Section: Introductionmentioning
confidence: 99%
“…Over a long treatment period for advanced NSCLC, tumor shape and volume may change and replanning is useful. Koay et al showed improvement of target coverage and sparing of the esophagus and spinal cord after adaptive planning especially for large tumors [52].…”
Section: Clinical Results Of Pbt For Advanced Nsclcmentioning
confidence: 99%